Poligami dalam Persepsi Keluarga Muslim di Kota Gorontalo - Muh. Ilham Alip (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2021)
The discourse on polygamy remains something that is widely discussed in society. The pros and cons of polygamy are not only a polemic among scholars but also a serious debate among Muslim families. This article aims to analyze the views of Muslim families in Gorontalo City towards polygamy and the factors that influence the views of Muslim families about polygamy. This research is qualitative research with a descriptive method. The approach used is sociological empirical. Data collection techniques in the form of observation, interviews, and documentation. Interviews were conducted with Muslim respondents in Gorontalo City with a purposive sample determination technique. The results of the study show that polygamy in the thinking of the Muslim community in Gorontalo City is an alternative that is carried out in an emergency or certain conditions, and also with some terms and conditions. In understanding the meaning of justice that must be achieved for a husband who practices polygamy, it is equity in terms of material, be it clothing, or food, not in the inclination of the heart or feelings. While polygamy gets a lot of negative views from Muslim families in Gorontalo City because polygamy seems only as a complement to inner instincts, and is far from the practice highlighted by the Prophet Muhammad saw.